The handling behaviour of off–road vehicles. (5th August 2014) - Horton, D.N.L.; Crolla, D.A.
Research relevant to the lateral dynamic behaviour of off–road vehicles is reviewed. This includes work on off–road vehicle dynamics and tyre forces, but the lateral behaviour of road vehicles is also reviewed where it is considered relevant. Although the lateral dynamics of road vehicles, both alone and in combinations, are fairly well understood, off–road vehicles have received little attention. It is concluded that the lack of lateral tyre force data in off–road conditions is the factor which at present limits the predictions of off–road handling and steering behaviour.